The Development of Mandarin Chinese Communication Skills through the Use of Lexically-based Teaching with Lexical Sets: การพัฒนาทักษะการสื่อสารภาษาจีนกลางด้วยการสอนแบบเน้นชุดคำศัพท์ - Prapagorn, Puthep (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2020)
The present study aimed at developing students’ Mandarin Chinese communication skills by the use of lexically-based teaching with lexical sets and examining the students’ satisfaction towards the teaching. The subject groups used in the study, obtained by purposive sampling was twenty-seven fourth years students who enrolled in Mandarin Chinese for Business. Since groups of students were suitable for implementing and learning with the teaching, this paper made use of quasi-experimental design with pre-test and post-test. The research instruments used for collecting the data were lesson plans and in-class exercises for Mandarin Chinese for Business, Mandarin Chinese communication achievement tests – pre and post-tests, and students’ satisfaction questionnaire towards the teaching. The research period was one semester with total of fifteen weeks. The teaching instruction was created into five productive phases namely, preparation, observation, learning, presentation, and conclusion. The findings revealed that the students’ Mandarin Chinese communication skills from groups was constantly improved with the statistical significance at the level of .05. Also, the finding in the satisfaction questionnaire showed that groups of student was satisfied with the instruction (=4.45, S.D.=0.27). The highest mean score from the questionnaire was that the teaching was very suitable for learning Mandarin Chinese. This indicted that the teaching could significantly increase the students’ Mandarin Chinese lexicon which led to effective communication. In addition, the teaching was motivated to learn, easy to understand, and the students were less concerned for grammatical mistakes. The students’ communication skills were more suitable and appropriate in different native-like contexts.